The Quaker Peace Testimony and its Contribution to the British Peace Movement: An Overview - Ceadel, Martin (Quaker studies, 2002)
This article attempts the first overview of the contribution of Quakerism to the British peace movement from its eighteenth-century origins to the present day. It emphasizes that the Society of Friends did much to make pacifism acceptable in Britain, and was the principal backer of the peace movement in the century following the end of the Napoleonic Wars. It shows how Quakers, although divided by the First World War and eclipsed by an upsurge in non-Quaker activism, reaffirmed their pacifism and did as much for the peace movement during the inter-war years as any small religious body could have done. And it argues that, as the peace movement lost momentum after the Second World War, Quakers played an increasingly important role despite an increasing diversity in their interpretation of their peace testimony.